ChatGPT for Teachers and Students in Science Learning: A Systematic Literature Review - Iwan Purnama; Firman Edi; Ruth Rize Paas Megahati S; Tiok Wijanarko (Jurnal Penelitian Pendidikan IPA, 2023)
In Indonesia Science education has not reached a portion that is in accordance with the needs of science education. Science learning should not only focus on knowledge but must also be balanced with application in everyday life. With this application, students will know that what they learn in science is applied and useful for life. That way, students will continue to try to experiment because of their high curiosity so that students are able to produce scientific products. Science problems are not only experienced by students, but teachers who teach science at school also have science problems they face. For this reason, Chat GPT (Generative Pre-Trainer Transformer) is used as one of the Open AI (Artificial Intelligence) innovations, a research company engaged in the development of artificial intelligence. The purpose of this research is to explain GPT Chat for Teachers and Students in Science Learning. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research show that Chat GPT has main functions, Chat GPT also has many uses for teachers and students, and science learning has five domains of science education, which must be supported by appropriate technological sophistication.